GMP-compliant production of (68Ga)Ga-NeoB for positron emission tomography imaging of patients with gastrointestinal stromal tumor - Pretze, Marc; Reffert, Laura; Diehl, Steffen J.; Schönberg, Stefan; Wängler, Carmen; Hohenberger, Peter; Wängler, Björn (EJNMMI radiopharmacy and chemistry, 2021)
[68Ga]Ga-NeoB is a novel DOTA-coupled Gastrin Releasing Peptide Receptor (GRPR) antagonist with high affinity for GRPR and good in vivo stability. This study aimed at (1) the translation of preclinical results to the clinics and establish the preparation of [68Ga]Ga-NeoB using a GMP conform kit approach and a licensed 68Ge/68Ga generator and (2) to explore the application of [68Ga]Ga-NeoB in patients with gastrointestinal stromal tumors (GIST) before and/or after interventional treatment (selective internal radiotherapy, irreversible electroporation, microwave ablation).
Im Titel ist der Ausdruck 68Ga in eckiger Klammer, dabei ist 68 hochgestellt
Gesehen am 20.06.2023